APENGARUH DATA OF ACCOUNT TERHADAP TINGKAT BAGI HASIL TABUNGAN DAN DEPOSITO MUDHARABAH (Studi Kasus Pada PT. Bank BNI Syariah SCO Langsa) - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2020)
This study aims to see the effect of Data of Account on the rate of profit sharing of savings and mudharabah deposits. Based on the results of the research and discussion that have been described in the previous chapter, it can be concluded that the Data of Accounts does not have a significant effect on the rate of profit sharing for savings and mudharabah deposits at PT. Bank BNI Syariah SCO Langsa. Based on the results of the study, the Data of account variable has a weak relationship with the growth of the rate of profit sharing for savings and mudharabah deposits at PT. Bank BNI Syariah SCO Langsa.